Longevity: Trends, uncertainty and the implications for pension systems - Frank Eich; Amarendra Swarup (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2009)
This paper presents historical trends in life expectancy in the United Kingdom and other countries and discusses how these trends might evolve over the coming decades. The paper argues that the expected increases in longevity are likely to have significant implications for the structure of pension systems in the future. Individuals, businesses and governments have already responded to these expected increases – for example by working longer, closing defined-benefit pension schemes or introducing parametric reforms to the state pension system – and are likely to change their behaviours further in the future. The issue is complicated by the fact that future longevity trends are uncertain. This makes it more difficult to allocate longevity risk efficiently and fairly across the different economic agents, while making it also more difficult to guarantee the sustainability of the system overall. The paper shows though that innovative solutions to this challenge are being developed, from businesses moving towards hybrid defined-benefit/defined-contribution pension schemes, to governments introducing mechanisms which automatically split the financial burden arising from future increases in life expectancy between state and individual, to businesses taking advantage of new products being developed to transfer any risk to the capital markets.
Keywords: 330; Pensions; Uncertainty; Financial markets; Longevity; Pension liabilities